The anatomy murders: being the true and spectacular history of Edinburgh's notorious Burke and Hare and of the man of science who abetted them in the commission of their most heinous crimes - Rosner, Lisa (Penn, Univ. of Pennsylvania Press)
The corpus delicti -- The anatomy wars -- Burking invented -- Sold to Dr. Knox -- Based on a true story -- The dangerous classes -- Anonymous subjects -- The criminal mind -- Crime scene : Edinburgh -- Day in court -- All that remains